Safety and Comparative Immunogenicity of an HIV-1 DNA Vaccine in Combination with Plasmid Interleukin 12 and Impact of Intramuscular Electroporation for Delivery - Kalams, Spyros A. (Oxford University Press, 2013)
Background. DNA vaccines have been very poorly immunogenic in humans but have been an effective priming modality in prime-boost regimens. Methods to increase the immunogenicity of DNA vaccines are needed. Methods. HIV Vaccine Trials Network (HVTN) studies 070 and 080 were multicenter, randomized, clinical trials. The human immunodeficiency virus type 1 (HIV-1) PENNVAX®-B DNA vaccine (PV) is a mixture of 3 expression plasmids encoding HIV-1 Clade B Env, Gag, and Pol. The interleukin 12 (IL-12) DNA plasmid expresses human IL-12 proteins p35 and p40. Study subjects were healthy HIV-1–uninfected adults 18–50 years old. Four intramuscular vaccinations were given in HVTN 070, and 3 intramuscular vaccinations were followed by electroporation in HVTN 080. Cellular immune responses were measured by intracellular cytokine staining after stimulation with HIV-1 peptide pools. Results. Vaccination was safe and well tolerated. Administration of PV plus IL-12 with electroporation had a significant dose-sparing effect and provided immunogenicity superior to that observed in the trial without electroporation, despite fewer vaccinations. A total of 71.4% of individuals vaccinated with PV plus IL-12 plasmid with electroporation developed either a CD4(+) or CD8(+) T-cell response after the second vaccination, and 88.9% developed a CD4(+) or CD8(+) T-cell response after the third vaccination. Conclusions. Use of electroporation after PV administration provided superior immunogenicity than delivery without electroporation. This study illustrates the power of combined DNA approaches to generate impressive immune responses in humans.